The Inverse Care Law programme: evaluating a population based intervention in primary care within deprived communities in Wales. - Song, Jiao; Akbari, Ashley; Cox, Caryn; May, Leon; Watkins, William; Aitken, Sarah; Thomas, Sarah; King, William (International Journal of Population Data Science, 2018)
Background The Inverse Care Law (ICL) programme was set up in South Wales valleys and aiming to achieve a measurable closing of the gap in health outcomes between the most and least deprived areas. Objectives People in deprived communities in Wales were invited for health checks to identify risks of cardiovascular disease followed by targeted interventions towards lifestyle risk factors, e.g. poor diet, physical inactivity, smoking and high alcohol intake, under the ICL programme piloted in Aneurin Bevan (AB) and Cwm Taf (CT) University Health Boards. Methods Welsh Longitudinal General Practice (WLGP) data held in Secure Anonymised Information Linkage (SAIL) databank was utilised to evaluate outcomes through project-specified clinical codes and uptake of the programme, linked with the Welsh Demographic Service Dataset (WDSD) providing demographic characteristics. Findings There were 7,094 people completing health checks in AB and CT University Health Boards between February 2015 and November 2016. 96% of these were in the three most deprived Welsh Index of Multiple Deprivation (WIMD) quintiles. 51% were referred within primary care for follow-up based on their health check results, 71% were overweight/obese, and 20% were identified as current smokers of within which 28% were referred to smoking sensation services, with further analyses to follow. Conclusions Implementations and effectiveness of the interventions and impact of health checks will be evaluated longitudinally on a scheduled basis with repeated analyses. Challenges and results will help refining the programme to be delivered across Wales.